Negative electrode sheet and preparation method thereof, sodium ion battery
By using a mesh support composed of hard carbon, carbon nanotubes and nanocellulose in sodium ion batteries, combined with the second active material, the adaptation problem of hard carbon and current collector is solved, and the circulation performance of sodium ion batteries is improved. Energy density enables the miniaturization and lightweight of the battery.
Patent Information
- Application Number
- CN202311030912.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-08-15
AI Technical Summary
In traditional sodium ion batteries, hard carbon and negative current collector are difficult to adapt, resulting in poor bonding performance of negative electrode sheets, limiting the use of hard carbon in sodium ion batteries.
Using a negative electrode sheet including hard carbon, carbon nanotubes and nanocellulose, a mesh support is formed by interweaving the carbon nanotubes and nanocellulose, and the hard carbon is dispersed therein, avoiding the use of current collectors, and combining the second active material to Improves gram capacity and structural stability.
The self-supporting performance and conductive properties of the negative electrode sheet are achieved, the adaptation problem of hard carbon and current collector is solved, the circulation performance and energy density of sodium ion batteries are improved, and the miniaturization and lightweight of the battery are promoted.
Smart Images

Figure CN117059740B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode plate and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the development of secondary batteries, sodium-ion batteries have received widespread attention due to their advantages such as abundant sodium resources and high battery stability. In sodium-ion batteries, hard carbon is a negative electrode active material with great advantages, such as abundant reserves, low cost, good conductivity, high theoretical sodium storage capacity, environmental friendliness and low redox potential.
[0003] In traditional sodium-ion batteries, the negative electrode sheet is usually prepared by compounding the negative electrode active layer including hard carbon with the current collector. However, due to the strong hydrophobicity of hard carbon, when combined with the commonly used aqueous binder, the negative electrode active layer and the current collector are prone to poor bonding performance, that is, hard carbon and the negative electrode current collector are difficult to adapt well, which in turn restricts the use of hard carbon in sodium-ion batteries. Summary of the invention
[0004] Based on this, the present application provides a negative electrode plate and a preparation method thereof, and a sodium ion battery. In the negative electrode plate, a negative electrode current collector may not be used, which better solves the problem that hard carbon in a traditional negative electrode plate is difficult to adapt to the negative electrode current collector.
[0005] A negative electrode plate comprises a first active material and a mesh support, wherein the first active material comprises hard carbon, the mesh support comprises carbon nanotubes and nanocellulose, the carbon nanotubes and nanocellulose are interwoven with each other, and the hard carbon is dispersed in the mesh support.
[0006] In some embodiments, the negative electrode sheet further includes a second active material, and the gram capacity of the second active material is greater than the gram capacity of the first active material.
[0007] In some embodiments, the second active material includes at least one of a silicon-based material, a tin-based material, and an antimony-based material.
[0008] In some embodiments, the second active material is bound to a portion of the surface of the carbon nanotube.
[0009] In some embodiments, the second active material is filled in the tubes of the carbon nanotubes.
[0010] In some embodiments, the second active material is coated on the outer surface of the carbon nanotube.
[0011] In some embodiments, the mass ratio of the second active material to the hard carbon is (3-5):10.
[0012] In some embodiments, the mass ratio of the nanocellulose, the carbon nanotubes and the hard carbon is (3-5):(2-5):10.
[0013] In some embodiments, the D50 of the hard carbon is 5 μm to 10 μm.
[0014] In some embodiments, the surface density of the hard carbon is 5 g / cm 2 ~15g / cm 2 .
[0015] In some embodiments, the carbon nanotube has a diameter of 10 nm to 20 nm.
[0016] In some embodiments, the carbon nanotubes have a length of 10 μm to 30 μm.
[0017] In some embodiments, the diameter of the nanocellulose is 30 nm to 50 nm.
[0018] In some embodiments, the length of the nanocellulose is 1 μm to 3 μm.
[0019] A method for preparing the negative electrode sheet comprises the following steps:
[0020] Preparing a solid phase mixture: mixing a precursor of a first active material, carbon nanotubes and nanocellulose, wherein the precursor of the first active material comprises a hard carbon precursor;
[0021] The solid phase mixture is subjected to a preforming process to obtain a preformed product;
[0022] The preformed product is subjected to a sintering process.
[0023] In some embodiments, the preparation of the solid phase mixture includes the following steps: mixing the precursor of the first active material, the carbon nanotubes, the nanocellulose and a dispersion containing a second active material to obtain a mixture, wherein the gram capacity of the second active material is greater than the gram capacity of the first active material; and performing solid-liquid separation on the mixture to obtain a solid phase product.
[0024] A sodium ion battery comprises the negative electrode sheet or the negative electrode sheet prepared by the preparation method.
[0025] In the above-mentioned negative electrode plate, carbon nanotubes and nanocellulose are interwoven to form a mesh support, and hard carbon is dispersed in the mesh support, which can make the negative electrode plate have better self-supporting performance and better conductive performance. As a result, a current collector is not required in the negative electrode plate, which effectively solves the problem of the difficulty in matching hard carbon and negative electrode current collector in traditional negative electrode plates.
[0026] In the above-mentioned method for preparing the negative electrode plate, a solid phase mixture is prepared by mixing a precursor of a first active material including a hard carbon precursor, carbon nanotubes and nanocellulose. In the obtained solid phase mixture, the carbon nanotubes and nanocellulose are intertwined to initially form a mesh support, and the hard carbon precursor is dispersed in the mesh support. Then, through a preforming treatment, the solid phase mixture can be preformed into the shape of a negative electrode plate. The preformed product is then sintered. During the sintering process, the carbon atoms in the hard carbon precursor are rearranged to form hard carbon in the mesh support. At the same time, during the sintering process, the mesh support structure is better fixed, and thus a negative electrode plate with better self-supporting performance can be formed.
[0027] In the above-mentioned sodium ion battery, the negative electrode plate has good structural stability, which can enable the sodium ion battery to maintain relatively stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the structure of the negative electrode sheet in one embodiment of the present application;
[0029] Figure 2 This is a SEM scanning electron microscope image of the self-supporting electrode of this application.
[0030] Description of the markings in the figure:
[0031] 10. Negative electrode; 101. Carbon nanotube; 102. Nanocellulose; 103. Hard carbon. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0033] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0036] See also Figure 1-2 , Figure 1 This is a schematic diagram of the macro state architecture of this application. Figure 2 Shown is a SEM scanning electron microscope image of a self-supporting electrode; the mesh support shown in the figure is composed of carbon nanotubes and nanocellulose interwoven with each other, and the slightly larger particles distributed thereon are hard carbon; and it can be seen that smaller particles of nano-type active materials are distributed on the surface of some carbon nanotubes and mesh supports.
[0037] An embodiment of the present application provides a negative electrode sheet 10. The negative electrode sheet 10 includes a first active material and a mesh support, the first active material includes hard carbon 103, the mesh support includes carbon nanotubes 101 and nanocellulose 102, the carbon nanotubes 101 and nanocellulose 102 are interwoven, and the hard carbon 103 is dispersed in the mesh support.
[0038] In the negative electrode plate of the present embodiment, carbon nanotubes and nanocellulose are interwoven to form a mesh support, and hard carbon is dispersed in the mesh support, so that the negative electrode plate can have better self-supporting performance and better conductive performance, thereby eliminating the need for a current collector in the negative electrode plate, and better solving the problem of the difficulty in matching hard carbon and the negative electrode current collector in traditional negative electrode plates.
[0039] Furthermore, in the negative electrode sheet of the present embodiment, the mesh support has a relatively large number of pores, which can promote the infiltration of the electrolyte into the negative electrode sheet, thereby facilitating the improvement of the battery cycle performance.
[0040] Furthermore, in the negative electrode sheet of the present embodiment, a current collector is not required, and the amount of active material used can be increased while the thickness of the negative electrode sheet remains unchanged. The density of the cross-linked network structure can be adjusted by adjusting the material ratio of nanocellulose and carbon nanotubes, so the specific surface area and structural strength can be adjusted to a certain extent to achieve the optimal battery performance design, which is conducive to improving the energy density of the battery. Alternatively, in the negative electrode sheet of the present embodiment, while keeping the amount of active material unchanged, since a current collector is not required, the overall thickness and weight of the negative electrode sheet can be reduced, which helps to promote the miniaturization and lightweight design of the battery.
[0041] Furthermore, in this embodiment, the hard carbon and the mesh support have a good bonding effect, so that the internal part of the negative electrode sheet can maintain good bonding performance without using a binder.
[0042] Furthermore, by using carbon nanotubes to selectively crosslink the active hydroxyl groups on the nanocellulose molecular chains, rigid hybrid crosslinking is performed within the structure, and the controllable preparation of self-supporting hard carbon with a crosslinked skeleton and abundant crosslinking nodes is achieved. The three-dimensional continuous conductive network provided by the carbon nanotubes in this structure facilitates the rapid transfer of electrons. At the same time, as an interconnected mechanical skeleton, it also ensures the stability of the electrode structure during repeated charge and discharge. The carbon nanotubes, as an electron transport layer, can effectively accelerate the transmission of electrons and improve the rate performance of the self-supporting hard carbon electrode; the hard carbon, as a sodium storage matrix, is conducive to the deintercalation of sodium ions. Since no binder is used, the pore structure and surface functional groups of the self-supporting hard carbon can be fully used for the storage of alkali metal ions, thereby giving full play to the structural advantages of the active material to maximize the electrochemical performance of the sodium ion battery.
[0043] Based on the fact that the negative electrode plate in this embodiment does not need to use a current collector and / or a binder, another embodiment of the present application provides a negative electrode plate without a current collector and / or a binder. The negative electrode plate without a current collector and / or a binder includes a first active material and a mesh support, the first active material includes hard carbon, the mesh support includes carbon nanotubes and nanocellulose, the carbon nanotubes and nanocellulose are interwoven, and the hard carbon is dispersed in the mesh support.
[0044] In some embodiments, the negative electrode plate is suitable for use in a sodium ion battery. In this embodiment, the negative electrode plate of the sodium ion battery includes a first active material and a mesh support, the first active material includes hard carbon, the mesh support includes carbon nanotubes and nanocellulose, the carbon nanotubes and nanocellulose are interwoven, and the hard carbon is dispersed in the mesh support.
[0045] It can be understood that, in the present application, hard carbon is dispersed in the mesh support body, which means that the hard carbon can be dispersed in the mesh of the mesh support body, and / or the hard carbon can also be dispersed on the surface of the mesh support body.
[0046] In some embodiments, the carbon nanotube tubes are filled with hard carbon. The hard carbon filled in the carbon nanotube tubes can further increase the amount of hard carbon used in the negative electrode sheet, which is beneficial to improve the energy density of the battery. In addition, the hard carbon filled in the carbon nanotube tubes can further improve the conductivity of the negative electrode sheet, promote the transmission of ions, and further improve the electrical performance of the battery.
[0047] In some embodiments, the negative electrode plate further includes a second active material, and the gram capacity of the second active material is greater than the gram capacity of the first active material. The second active material has a higher gram capacity, and introducing the second active material into the negative electrode plate can further improve the energy density of the battery.
[0048] Optionally, the second active material includes at least one of a silicon-based material, a tin-based material, and an antimony-based material. Optionally, the silicon-based material includes at least one of elemental silicon and silicon oxide. Optionally, the tin-based material includes at least one of elemental tin and tin oxide. Optionally, the antimony-based material includes at least one of elemental antimony and antimony oxide.
[0049] Further, the particle size of the second active material is nanometer-scale. For example, the D50 of the second active material is 20nm to 30nm. Optionally, the D50 of the second active material can be 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, etc.
[0050] In some embodiments, the second active material is bound to a portion of the surface of the carbon nanotube. The second active material has the advantage of a higher gram capacity, but it often has a larger expansion rate. During the charge and discharge cycle of the battery, the volume of the negative electrode plate may increase, causing the negative electrode plate to pulverize and crack, and each crack formed will also cause a new interface to be generated, and the SEI (solid electrolyte) consumption will increase sharply, resulting in battery performance degradation and reduced safety. Carbon nanotubes have good mechanical properties. The second active material is bound to a portion of the surface of the carbon nanotubes. The carbon nanotubes can buffer the expansion of the second active material, reduce the risk of an increase in the volume of the negative electrode plate due to the expansion of the second active material, and help the negative electrode plate maintain a good structural stability during the use of the battery, thereby further improving the electrical performance of the battery. Optionally, the second active material is coated on the outer surface of the carbon nanotube. Further optionally, the second active material is filled in the pipe of the carbon nanotube.
[0051] It can be understood that, in some embodiments, the outer surface of the carbon nanotube is coated with the second active material, and the interior of the carbon nanotube is also filled with the second active material.
[0052] In some embodiments, the mass ratio of the second active material to the hard carbon is (3-5):10. Within this mass ratio range, the mass ratio of the second active material to the hard carbon can be well adapted, so that the negative electrode plate maintains a high energy density while maintaining good structural stability. Optionally, the mass ratio of the second active material to the hard carbon can be 3:10, 3.5:10, 4:10, 4.5:10, 5:10, etc.
[0053] In some embodiments, the mass ratio of nanocellulose, carbon nanotubes and hard carbon is (3-5): (2-5): 10. The mass ratio of nanocellulose, carbon nanotubes and hard carbon within this range can form a more stable mesh support, which is beneficial to further improve the self-supporting performance of the negative electrode sheet and maintain better structural stability of the negative electrode sheet. At the same time, the mass ratio of nanocellulose, carbon nanotubes and hard carbon within this range can make the negative electrode sheet have a higher energy density. Furthermore, by setting the mass ratio of nanocellulose, carbon nanotubes and hard carbon within this range, the battery can have both higher energy density and better cycle stability.
[0054] As some optional examples of the mass ratio of nanocellulose, carbon nanotubes and hard carbon, the mass of nanocellulose, carbon nanotubes and hard carbon can be 3:2:10, 3:3:10, 3:4:10, 3:5:10, 4:2:10, 4:3:10, 4:4:10, 4:5:10, 5:2:10, 5:3:10, 5:4:10, 5:5:10, etc.
[0055] In some embodiments, the D50 of the hard carbon is 5 μm to 10 μm. The particle size of the hard carbon within this range can be well dispersed in the mesh support. At the same time, the hard carbon within this range has a strong adsorption bonding force with the mesh support, which can make the bonding between the hard carbon and the mesh support more stable, which is conducive to further improving the structural stability of the negative electrode sheet.
[0056] In some embodiments, the hard carbon has an area density of 5 g / cm 2 ~15g / cm 2 The hard carbon surface density within this range can make the negative electrode sheet have a higher energy density. If the hard carbon surface density is too high, the risk of powder loss of the negative electrode sheet may increase. Optionally, the hard carbon surface density can be 5g / cm 2 , 6g / cm 2 , 7g / cm 2 , 8g / cm 2 , 9g / cm2 、10g / cm 2 , 11g / cm 2 , 12g / cm 2 , 13g / cm 2 , 14g / cm 2 , 15g / cm 2 wait.
[0057] In some embodiments, the diameter of the carbon nanotube is 10nm to 20nm. The carbon nanotube within this diameter range has a suitable channel space, which is conducive to the filling of hard carbon and / or the second active material inside the channel of the carbon nanotube, and can further improve the performance of the negative electrode sheet. Optionally, the diameter of the carbon nanotube can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, etc.
[0058] In some embodiments, the length of the carbon nanotube is 10 μm to 30 μm. Carbon nanotubes with a length within this range can further improve the stability of the mesh support and improve the self-supporting performance of the negative electrode sheet. Optionally, the length of the carbon nanotube can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.
[0059] In some embodiments, the diameter of the nanocellulose is 30nm to 50nm. The length of the nanocellulose is 1μm to 3μm. The diameter and / or length of the nanocellulose within the corresponding range can make the interweaving of the nanocellulose and the carbon nanotubes more stable, which can further improve the stability of the mesh support and improve the self-supporting performance of the negative electrode. Optionally, the diameter of the nanocellulose can be 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, etc. Optionally, the length of the nanocellulose can be 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, etc.
[0060] Another embodiment of the present application provides a method for preparing a negative electrode plate, comprising the following steps: preparing a solid phase mixture: mixing a precursor of a first active material, carbon nanotubes and nanocellulose, wherein the precursor of the first active material includes a hard carbon precursor; pre-forming the solid phase mixture to obtain a pre-formed product; and sintering the pre-formed product.
[0061] In the preparation method of this embodiment, a solid phase mixture is prepared by mixing a precursor of a first active material including a hard carbon precursor, carbon nanotubes and nanocellulose. In the obtained solid phase mixture, the carbon nanotubes and nanocellulose are intertwined to initially form a mesh support, and the hard carbon precursor is dispersed in the mesh support. Then, through a preforming treatment, the solid phase mixture can be preformed into the shape of a negative electrode sheet. The preformed product is then sintered. During the sintering process, the carbon atoms in the hard carbon precursor are rearranged to form hard carbon in the mesh support. At the same time, during the sintering process, the mesh support structure is better fixed, and then a negative electrode sheet with better self-supporting performance can be formed.
[0062] In some embodiments, the temperature of the sintering process is 1000° C. to 1600° C. The temperature of the sintering process within this range can further promote the rearrangement of carbon atoms in the hard carbon precursor. Alternatively, the sintering temperature of the sintering process can be 1000° C., 1100° C., 1200° C., 1300° C., 1400° C., 1500° C., 1600° C., etc.
[0063] Further optionally, the sintering time is 2 hours to 8 hours. For example, the sintering time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0064] It is understandable that the sintering process is carried out under a protective gas atmosphere. Optionally, the protective gas may be at least one of argon, nitrogen, helium and neon.
[0065] In some embodiments, the preforming process can be performed by rolling. For example, the solid phase mixture is subjected to rolling process to form the solid phase mixture into the shape of a negative electrode sheet, thereby obtaining a preformed negative electrode sheet, that is, a preformed product.
[0066] In some embodiments, preparing a solid phase mixture comprises the following steps: mixing a precursor of a first active material, carbon nanotubes, nanocellulose and a dispersion containing a second active material to obtain a mixture, wherein the gram capacity of the second active material is greater than the gram capacity of the first active material; and subjecting the mixture to solid-liquid separation to obtain a solid phase product. By introducing a dispersion containing the second active material, the second active material can be bound to a portion of the surface of the carbon nanotube. It is understood that the second active material can be bound to a portion of the surface of the carbon nanotube by coating the second active material on the outer surface of the carbon nanotube, or by filling the second active material in the pipe of the carbon nanotube. Optionally, the second active material comprises at least one of a silicon-based material, a tin-based material and an antimony-based material. It is understood that the dispersant in the dispersion can be water.
[0067] In some embodiments, when the precursor of the first active material, carbon nanotubes, nanocellulose and the dispersion containing the second active material are mixed, the mixing uniformity can be improved by ultrasonic dispersion, stirring dispersion, etc., so that the dispersion fully infiltrates the precursor of the first active material. It is understood that the mixture is obtained after treatment by ultrasonic dispersion, stirring dispersion, etc.
[0068] In some embodiments, solid-liquid separation can be performed by combining suction filtration and freeze drying. For example, the mixture can be first subjected to suction filtration, and then the filter cake obtained by the suction filtration can be freeze dried.
[0069] Optionally, the mass ratio of nanocellulose to carbon nanotubes is (3-5): (2-5). Further optionally, the mass ratio of nanocellulose to carbon nanotubes can be 3:2, 3:3, 3:4, 3:5, 4:2, 4:3, 4:5, 5:2, 5:3, 5:4, etc. Nanocellulose and carbon nanotubes are the main supporting materials constituting the negative electrode of the present application. The structure formed by them is a mesh body. The ratio affects the distribution and mechanical properties of the mesh body, and they cooperate with the hard carbon material to form the whole negative electrode sheet. The hard carbon material is the main active substance, and its proportion is also directly related to the capacity of the negative electrode sheet. Therefore, the ratio of nanocellulose and carbon nanotubes needs to be balanced and adjusted.
[0070] In some embodiments, the hard carbon precursor may be a biomass carbon material. Optionally, the biomass carbon material may be at least one of rice husks, corn cobs, pumpkin vines, coconut shells, reed flowers, loofahs, wheat straws, camphor wood, bamboo, willow, peach wood, and rosewood.
[0071] Further, the hard carbon precursor can be a biomass material after pre-carbonization treatment. Optionally, the temperature of the pre-carbonization treatment is 350°C to 700°C. The time of the pre-carbonization treatment is 2h to 8h. Further optionally, the temperature of the pre-carbonization treatment can be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc. It is understood that the pre-carbonization treatment is carried out under a protective gas atmosphere. Optionally, the protective gas can be at least one of argon, nitrogen, helium and neon.
[0072] In some embodiments, the method for preparing the negative electrode sheet includes:
[0073] S01: Under a protective gas atmosphere, pre-carbonizing the biomass carbon material to obtain a hard carbon precursor.
[0074] S02: Adding carbon nanotubes and nanocellulose into a dispersion containing a second active material.
[0075] S03: The hard carbon precursor obtained in S01 is added to the dispersion liquid of S02 and mixed to obtain a mixture.
[0076] S04: subjecting the mixture obtained in S03 to solid-liquid separation to obtain a solid phase mixture.
[0077] S05: The solid phase mixture obtained in S04 is subjected to preforming treatment to obtain a preformed product.
[0078] S06: Under a protective gas atmosphere, the preformed product is sintered at 1000° C. to 1600° C.
[0079] Another embodiment of the present application provides a sodium ion battery, comprising the above-mentioned negative electrode sheet or the negative electrode sheet prepared by the above-mentioned preparation method. The negative electrode sheet has good structural stability, thereby enabling the sodium ion battery to maintain relatively stable cycle performance.
[0080] It is understandable that the sodium ion battery further comprises a positive electrode plate, a separator and an electrolyte, wherein the separator and the electrolyte are located between the positive electrode plate and the negative electrode plate.
[0081] Another embodiment of the present application provides an electrical device including the above-mentioned sodium ion battery.
[0082] Example
[0083] Example 1
[0084] The preparation method of the negative electrode sheet in this embodiment is as follows:
[0085] S101: Under a protective gas atmosphere, the coconut shell is pre-carbonized at a temperature of 350° C. and for 4 hours to obtain a hard carbon precursor.
[0086] S102: 3 g of carbon nanotubes and 3 g of nanocellulose are added into 20 g of 15% by mass nano-tin dioxide dispersion to fully disperse and infiltrate.
[0087] S103: Take 10 g of the hard carbon precursor obtained in S101 and add it into the dispersion liquid of S102 to mix them to obtain a mixture.
[0088] S104: The mixture obtained in S103 is filtered and freeze-dried to obtain a solid phase mixture.
[0089] S105: The solid phase mixture obtained in S104 is subjected to preforming treatment to obtain a preformed product.
[0090] S106: In a protective gas atmosphere, the preformed product is sintered at 1200°C for 4 hours to obtain a negative electrode plate. The negative electrode plate includes 10g of hard carbon, 3g of carbon nanotubes and 3g of nanocellulose. The carbon nanotubes and nanocellulose are interwoven to form a mesh support, and the hard carbon is dispersed in the mesh support. The D50 of the hard carbon is 7μm, and the surface density of the hard carbon is 9g / cm 2 .
[0091] Example 2
[0092] Compared with Example 1, the differences of this example are: 3 g of carbon nanotubes, 2 g of nanocellulose, and 10 g of hard carbon.
[0093] Example 3
[0094] Compared with Example 1, the differences of this example are: 5 g of carbon nanotubes, 5 g of nanocellulose, and 10 g of hard carbon.
[0095] Example 4
[0096] Compared with Example 1, the difference of this embodiment is that the finished negative electrode sheet contains 5g of nano-tin dioxide in terms of mass ratio, that is, the mass ratio of nano-tin dioxide: hard carbon is 5:10.
[0097] Example 5
[0098] Compared with Example 1, the difference of this embodiment is that: nano-tin dioxide is replaced by antimony oxide; antimony oxide dispersion is added so that the finished negative electrode sheet contains 5g of antimony oxide by mass ratio; that is, the mass ratio of antimony oxide: hard carbon is 5:10.
[0099] Example 6
[0100] The preparation method of the negative electrode sheet in this embodiment is as follows:
[0101] S101: Under a protective gas atmosphere, the coconut shell is pre-carbonized at a temperature of 350° C. and for a time of 4 hours to obtain a hard carbon precursor.
[0102] S102: 3 g of carbon nanotubes and 3 g of nanocellulose are mixed with 10 g of the hard carbon precursor obtained in S101 to obtain a solid phase mixture.
[0103] S103: The solid phase mixture obtained in S102 is subjected to preforming treatment to obtain a preformed product.
[0104] S104: In a protective gas atmosphere, the preformed product is sintered at 1200°C for 4 hours to obtain a negative electrode plate. The negative electrode plate includes 10g of hard carbon, 3g of carbon nanotubes and 3g of nanocellulose. The carbon nanotubes and nanocellulose are interwoven to form a mesh support, and the hard carbon is dispersed in the mesh support. The D50 of the hard carbon is 7μm, and the surface density of the hard carbon is 9g / cm 2 That is, compared with Example 1, no second active material is added.
[0105] Comparative Example 1
[0106] Compared with Example 1, the differences of this example are: 3 g of carbon nanotubes, 0 g of nanocellulose, and 10 g of hard carbon.
[0107] Comparative Example 2
[0108] Compared with Example 1, the differences of this example are: 0 g of carbon nanotubes, 3 g of nanocellulose, and 10 g of hard carbon.
[0109] Comparative Example 3
[0110] The difference from Example 1 is that a conventional coating method is used to coat the negative electrode active slurry on the negative electrode current collector to form a negative electrode sheet, and the active material in the negative electrode slurry is hard carbon.
[0111] Preparation of batteries.
[0112] (1) Positive electrode: metallic sodium plate.
[0113] (2) Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and NaPF6 was added to form an electrolyte, and the concentration of NaPF6 was 1 mol / L;
[0114] (3) Separation membrane: polypropylene microporous membrane.
[0115] (4) Negative electrode sheet: the negative electrode sheet in the embodiments and comparative examples.
[0116] Assemble button-type sodium-ion batteries in an inert atmosphere glove box according to the assembly order of negative electrode sheet, separator, electrolyte, and positive electrode sheet.
[0117] Sodium-ion battery testing.
[0118] (1) The sodium ion battery was subjected to rate performance tests. The assembled button sodium ion battery was subjected to constant current charge and discharge tests at a rate of 0.2C in a voltage range of 0-1.5V, and its first charge and discharge capacity was recorded, and the first coulomb efficiency was calculated. After three cycles at this rate, the constant current charge and discharge test was adjusted to 5C rate, and its charge and discharge capacity was recorded. The capacity retention rate at 5C rate compared with 0.2C was calculated. The test results are shown in Table 1.
[0119] (2) The sodium ion batteries were tested for cycle performance. The assembled button-type sodium ion batteries were tested for 100 cycles at a voltage range of 0-1.5 V and a rate of 2C, and the capacity retention rate of the 100th cycle compared to the first cycle was calculated. The test results are shown in Table 1.
[0120] Table 1
[0121]
[0122] From Table 1 we can see that:
[0123] (1) From the comparison between Examples 1 to 6 and Comparative Example 3, it can be seen that the batteries corresponding to Examples 1 to 6 using the self-supporting negative electrode sheets have higher capacity and better cycle performance than the batteries corresponding to the conventional negative electrode current collector coating. This indicates that the self-supporting negative electrode sheets in Examples 1 to 6 are beneficial to improving the capacity and cycle performance of the battery.
[0124] (2) From the comparison between Examples 1 to 5 and Comparative Examples 1 to 2, it can be seen that in Examples 1 to 5, the mass ratio of nanocellulose, carbon nanotubes and hard carbon is in the range of (3-5): (2-5): 10, and the corresponding batteries have better cycle performance; more specifically, based on the mass of hard carbon, the masses of carbon nanotubes and nanocellulose are adjusted so that the structure serving as the network support in the negative electrode sheet accounts for a larger proportion, such as in Examples 1 and 3, the 0.2C capacity thereof is slightly decreased, but the network support structure is more stable and has excellent mechanical properties, so the cycle performance is improved. On the contrary, as in Examples 1 and 2, the mass proportion of nanocellulose is decreased, so its cycle performance is affected.
[0125] (3) From the comparison between Examples 1 to 5 and 6, it can be seen that when the negative electrode sheet includes the second active material, the battery has a higher capacity; specifically, referring to Examples 1, 4 and 6, tin dioxide is used as a high specific volume material, so increasing the proportion of tin dioxide in the negative electrode material can effectively increase the capacity, but since tin dioxide is prone to expansion and powdering during the charge and discharge process, it is also easy to cause the appearance of new interfaces and react with the electrolyte to form SEI, resulting in a decrease in the first efficiency. However, tin dioxide is effectively restricted by the three-dimensional network structure composed of carbon nanotubes and nanocellulose in the present application, which can limit the volume expansion change of the second active material and stabilize the overall structure of the negative electrode sheet; although its cycle performance is reduced and the first efficiency performance is also affected, its capacity is effectively improved, which is an excellent means of using high expansion and high specific volume materials.
[0126] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0127] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the specification and drawings may be used to interpret the contents of the claims.
Claims
1. A negative electrode plate, characterized in that: The invention comprises a first active material and a mesh support, wherein the first active material comprises hard carbon, the mesh support comprises carbon nanotubes and nanocellulose, the carbon nanotubes and nanocellulose are interwoven with each other, and the hard carbon is dispersed in the mesh support; The negative electrode sheet further includes a second active material, wherein the gram capacity of the second active material is greater than the gram capacity of the first active material; The second active material includes at least one of a silicon-based material, a tin-based material, and an antimony-based material; The carbon nanotube tubes are filled with the second active material; The D50 of the second active material is 20nm~30nm; The diameter of the carbon nanotubes is 10nm-20nm.
2. The negative electrode sheet according to claim 1, characterized in that: The outer surface of the carbon nanotube is coated with the second active material.
3. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the second active material to the hard carbon is (3-5):
10.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The mass ratio of the nanocellulose, the carbon nanotubes and the hard carbon is (3-5):(2-5):
10.
5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The D50 of the hard carbon is 5 μm to 10 μm; and / or, The surface density of the hard carbon is 5 g / cm 2 ~15g / cm 2 and / or, The length of the carbon nanotubes is 10 μm to 30 μm and / or The diameter of the nanocellulose is 30nm to 50nm; and / or, The length of the nanocellulose is 1 μm to 3 μm.
6. A method for preparing a negative electrode sheet according to any one of claims 1 to 5, characterized in that: The steps include: Preparing a solid phase mixture: mixing a precursor of the first active material, the carbon nanotubes, the nanocellulose, and a dispersion containing a second active material to obtain a mixture, wherein the gram capacity of the second active material is greater than the gram capacity of the first active material; performing solid-liquid separation on the mixture to obtain a solid phase mixture; The solid phase mixture is subjected to a preforming process to obtain a preformed product; The preformed product is subjected to a sintering process.
7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The hard carbon precursor includes a biomass material.
8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The biomass material comprises at least one of rice husk, corn cob, pumpkin vine, coconut shell, reed flower, loofah, wheat straw, camphor wood, bamboo wood, willow wood, peach wood and rosewood.
9. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The hard carbon precursor includes the biomass material after pre-carbonization treatment; the temperature of the pre-carbonization treatment is 350° C. to 700° C., and the time of the pre-carbonization treatment is 2 hours to 8 hours.
10. A sodium ion battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 5 or a negative electrode sheet prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Three-dimensional mesh structure form electrode for electrochemical device, method for producing same, and electrochemical device comprising same
CN107873104A
Preparation method and application of flexible composite electrode
CN109285991A
Electrochemical active material as well as preparation method and application thereof
CN115332515A